Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.mimet.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide sequences forming short self-complimentary hairpins can expedite the down-regulation of Coprinopsis cinerea genes

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. This technological advance should expedite functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Liquid-grown cultures were successfully protoplasted using Trichoderma sp. lysing enzyme, generating in excess of 10 8 protoplasts from a single flask culture. Protoplasts transformed with plasmids containing either the full-length hph gene (pPHT1, pMhph004, and pMhphi004) or the truncated hph gene (pAN7-1, phph004, and phphi004) in the presence of PEG-CaCl 2 were screened for the hygromycin-resistant colonies on PDAS plates overlaid with hygromycin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid-grown cultures were successfully protoplasted using Trichoderma sp. lysing enzyme, generating in excess of 10 8 protoplasts from a single flask culture. Protoplasts transformed with plasmids containing either the full-length hph gene (pPHT1, pMhph004, and pMhphi004) or the truncated hph gene (pAN7-1, phph004, and phphi004) in the presence of PEG-CaCl 2 were screened for the hygromycin-resistant colonies on PDAS plates overlaid with hygromycin.…”
Section: Resultsmentioning
confidence: 99%
“…Many wild isolates of basidiomycetes are dikaryotic and this also reduces the utility of such a method, given the likely difficulty of disrupting the desired target in both nuclear types. RNAi-mediated gene silencing is an alternative mechanism to targeted gene disruption and has already been established in species such as C. cinerea, A. bisporus, and S. commune, with the advantage that targeted insertion is not necessary and that it is likely to deplete specific transcripts irrespective of nuclear origin (8,9,18,37,56) so it would be phenotypically dominant.…”
mentioning
confidence: 99%
“…Nevertheless, these data clearly demonstrated that RNA silencing can be efficiently induced by direct physical delivery of dsRNA into the cell (Caribé dos Santos et al, 2009). Similarly, in Coprinopsis cinerea the commercially available pSUPER RNAi System™ (OligoEngine™, USA) was tested (Costa et al, 2008). This system is based on a short hpRNA construct comprising a user defined sense and antisense target sequence separated by a 9 nt spacer.…”
Section: Rna Silencing As Defense Against Invasive Nucleic Acidsmentioning
confidence: 99%
“…The efficacy of a 19 nt stem length construct at inducing gfp silencing was investigated. Not unexpectedly, the efficiency of silencing was found to vary, with one strain showing an almost complete loss of gfp expression (Costa et al, 2008).…”
Section: Rna Silencing As Defense Against Invasive Nucleic Acidsmentioning
confidence: 99%
“…RT-qPCR analyses indicated that transcripts of two Agaricus bisporus genes (URA3 and CBX) silenced with hairpin constructs were significantly reduced (Costa et al, 2009). In Coprinopsis cinerea, Costa et al (2008) reported that the use of short hairpin constructs promoted the formation of transformants with reduced transcripts of the Green Fluorescent Protein (GFP) transgene.…”
Section: Introductionmentioning
confidence: 99%